DARI TEKS HADIS KE KONTEKS BISNIS: HERMENEUTIKA TRANSPARANSI EKONOMI - Mohammad Salahuddin Al-Ayyuubi; Faridatuz Zakiyah (Al-Bayan: Journal of Hadith Studies, 2023)
The rapid expansion of e-commerce in Indonesia has created a significant paradox, offering unprecedented convenience while simultaneously causing a surge in consumer disputes due to information asymmetry. This situation highlights a systemic crisis of trust, demanding a robust ethical framework. This article aims to address this ethical gap by reinterpreting the classical hadith of Hakim bin Hizam on trade transparency for the modern digital business context, demonstrating the enduring relevance of Islamic economic ethics. This library research employs an integrated hermeneutical framework, combining the classical hadith sciences of takhrij and ma’anil hadis with Fazlur Rahman’s Double Movement theory and Paul Ricoeur’s Three Worlds model. This approach facilitates a dynamic interpretation that bridges the 7th-century text with 21st-century e-commerce realities. The analysis recontextualizes key hadith concepts: physical separation (tafarruq) is interpreted as the temporal window of a return policy; lying and concealing (katamā wa kadhabā) correspond to modern information asymmetry, tadlis, and manipulative dark patterns; and the right of choice (khiyār) is actualized in marketplace features like cancellation and dispute resolution. The concept of “blessing” (barakah) is correlated with market efficiency and consumer trust. The hadith of Hakim bin Hizam is not an obsolete text but a dynamic ethical charter for the digital economy. It provides a sophisticated framework for building a more transparent, just, and sustainable e-commerce ecosystem, reframing consumer protection as a moral pursuit of barakah.